A multilevel Monte Carlo algorithm for SDEs with jumps - Rantala, Johanna (2019)
The multilevel Monte Carlo algorithm is an extension of the traditional Monte Carlo algorithm. It is a numerical method, which allows us to approximate the expected value of a random variable X. We use some appropriate discretization method to obtain approximations X_1, X_2, ... ,X_L of X such that each approximation is made with a finer grid. The more accuracy we want from our approximation, the more the computational cost grows. The multilevel method exploits evaluation at multiple levels of refining discretizations allowing us to achieve a better accuracy with lower cost.